"Something Tells Me I Can't Do That No More": Experiences With Real-Time Glucose and Activity Monitoring Among Underserved Black Women With Type 2 Diabetes. Issue 2 (April 2022) - Fritschi, Cynthia; Kim, Min Jung; Srimoragot, Manassawee; Jun, Jeehye; Sanchez, Lidia Emily; Sharp, Lisa K.
Purpose: The purpose of the study was to explore self-regulation skills with real-time activity and glucose monitoring among Black women with type 2 diabetes (T2DM). Methods: A small acceptability trial was conducted using technology (continuous glucose monitors and Fitbit) to facilitate core behaviors associated with self-regulation (self-monitoring/assessment, learning, mental contrasting [comparing current values with goal values], and goal setting/review). Participants were given continuous glucose monitors and Fitbit activity trackers for self-monitoring of blood glucose and activity. Two sessions of group diabetes education were also offered. Following the intervention, semistructured interviews and subsequent content analyses were conducted to explore how the women's experiences reflected certain self-regulation behaviors. Results: Eight underserved Black women with non-insulin-requiring T2DM were included (age = 68 ± 5.2 years; A1C = 6.6% ± 1.1%; 15.3 ± 7.2 years since diagnosis). Content analysis revealed themes that were consistent with core self-regulation behaviors: experiential learning through self-monitoring, mental contrasting, and impact on behavior (actual behavior change and motivation to change behavior). Conclusions: With use of real-time glucose and activity monitoring, underserved Black women with T2DM described how they used the data from the devices to make choices about eating and activity behaviors.